Objective financial toxicity in patients with cancer: a cross-sectional study - Nguyen, Thanh Xuan; Tran, Binh Thang; Hoang, Trong Nhat (Tạp chí Y Dược Huế, 2025)
Introduction: We conducted this study to estimate the objective financial toxicity and identify the associated factors that contribute to the objective financial toxicity among patients with cancer. Methods: A cross-sectional study that included 300 patients was carried out at Hue Central Hospital, Vietnam from 09/2022 to 03/2023. Data was collected using a structured questionnaire through face-to-face interviews and review of medical records. Objective financial toxicity was measured by catastrophic health expenditure (CHE), threshold of 25% of average household income. A multivariable logistic model was used to determine the factors that contribute to CHE in patients with cancer. Results: The prevalence of CHE at cutoff points 25% was 85.7%. The higher risk of CHE was significantly associated with age under 60 (OR = 1.93, 95% CI: 1.05 - 3.52); female (OR = 3.34, 95% CI: 1.74 - 6.40); no income (OR = 4.03, 95% CI: 1.40 - 11.6); stage III (OR = 6.94, 95% CI: 1.01 - 47.56), respectively. In contrast, no significant association was found between health insurance, residential areas, education level, or cancer type and CHE. Conclusions Our study and existing research highlight the significant financial burden borne by cancer patients (CHE, 85.7%), particularly those with lower socioeconomic status and in later stage of the disease